KARAKTER FENOTIPE TANAMAN KRISAN (DENDRANTHEMA GRANDIFLORUM) KULTIVAR BIG YELLOW HASIL PERLAKUAN KOLKISIN - Daryono, Budi Setiadi; Rahmadani, Wenny Deisshinta (JURNAL AGROTROPIKA, 2009)
Chrysanthemum (Dendranthema grandiflorum) is well known as a commercially valuable flower. However, the plant cultivation has not been well developed. Poliploidization is one of cultivation technique using colchicines as mutagenic agent to produce high quality of flowers. The aims of this research were to study phenotypic characters of chrysanthemum treated by colchicines and to determine the optimum of soaking time to obtain the highly phenotypic characters.Colchicines concentration used in this research was 0.01% with soaking times were 6, 12 and 24 hours. Phenotypic characters observed in this experiment were flower diameter, plant height, stem diameter, long and wide of 5th and 10th leaf from flower base with 10 replications for each characters.The result showed that soaking times treatment with 0.01% colchicines have real influence on flower diameter, plant height, stem diameter, long and wide of 5th and 10th leaf from flower base. The result of colchicines with soaking treatment of 12 hours showed the highly phenotypic characters. In addition, chrysanthemum with colchicines treatment has bigger phenotypic characters than control. Key words: Chrysanthemum, Dendranthema grandiflorum, colchicines, phenotypic characters